Key functional groups affecting the release of gaseous products during spontaneous combustion of coal - Jing-yu ZHAO; Yong-li ZHANG; Jun DENG; Jia-jia SONG; Tao WANG; Yan-ni ZHANG; Yu-xuan ZHANG (工程科学学报, 2020)
Coal–oxygen reaction theory, which is widely accepted, considers the reaction of coal and oxygen during combustion. In this research, the characteristics of spontaneous coal combustion were assessed at a high temperature to investigate the internal relationship between the gaseous products of this reaction and the functional groups in coal molecules and to further reveal the micro-characteristics of spontaneous coal combustion. Our self-developed temperature-programmed experimental system and in situ diffuse reflectance infrared Fourier transform spectroscopy were adopted to analyze the correlation between the contents of gaseous products and active functional groups. Results reveal that the contents of indicator gases, such as CO and C2H4, increase and show a parabolic curve. In terms of active functional groups, as temperature increases, the content of aliphatic hydrocarbons initially increases and then decreases gradually. The content of C=C groups decreases throughout this study, and the content of oxygen-containing functional groups gradually increases after equilibrium is reached. Five characteristic temperatures are obtained on the basis of the variation in gaseous products, and four oxidation stages are further divided. The relationship between active functional groups and gases during different temperature stages is determined. At the critical temperature stage, the main active functional group affecting the release of CO, CO2, CH4, and C2H6 is carbonyl. Numerous alkyl chains and bridge bonds are broken at the crack‒active‒speedup temperature stage, and the primary active functional groups influencing the gas products are aliphatic hydrocarbons and carbonyl groups. The concentration of gases at the speedup‒ignition temperature stage is negatively correlated with carbonyl and carboxyl groups. Therefore, the crack‒active‒speedup temperature stage in high-temperature oxidation is dangerous, and oxidation should be controlled before this stage to reduce the loss of personnel and materials.